Housekeeping mutualisms: do more symbionts facilitate host performance? - Adrian C Stier; Michael A Gil; C Seabird McKeon; Sarah Lemer; Matthieu Leray; Suzanne C Mills; Craig W Osenberg (PLoS ONE)
Mutualisms often involve one host supporting multiple symbionts, whose identity, density and intraguild interactions can influence the nature of the mutualism and performance of the host. However, the implications of multiple co-occurring symbionts on services to a host have rarely been quantified. In this study, we quantified effects of decapod symbionts on removal of sediment from their coral host. Our field survey showed that all common symbionts typically occur as pairs and never at greater abundances. Two species, the crab Trapezia serenei and the shrimp Alpheus lottini, were most common and co-occurred more often than expected by chance. We conducted a mesocosm experiment to test for effects of decapod identity and density on sediment removal. Alone, corals removed 10% of sediment, but removal increased to 30% and 48% with the presence of two and four symbionts, respectively. Per-capita effects of symbionts were independent of density and identity. Our results suggest that symbiont density is restricted by intraspecific competition. Thus, increased sediment removal from a coral host can only be achieved by increasing the number of species of symbionts on that coral, even though these species are functionally equivalent. Symbiont diversity plays a key role, not through added functionality but by overcoming density limitation likely imposed by intraspecific mating systems.